1996
DOI: 10.1021/om9601099
|View full text |Cite
|
Sign up to set email alerts
|

XPS Investigations of (1,4,7-trimethyl-1,4,7-triazacyclononane)RhMe3and [1,1,1-tris((dimethylphosphino)methyl)ethane]RhMe3and Their Rh−C Cleavage Derivatives. Comparison of Hard- and Soft-Ligated Rhodium Organometallics

Abstract: The new molecules P3RhMe3-n (OTf) n are reported (n = 0−2; P3 = MeC(CH2PMe2)3; OTf = OS(O)2CF3). The known fac-(Me3P)3RhMe3 was converted to mer-(Me3P)3RhMe3-n Cl n (n = 1, 2) by cleavage with HCl in ether. X-ray photoelectron spectra (XPS) of these were recorded, and all except the P3RhMe3-n Cl n series afforded clean spectra. XPS were also obtained for the known CnRhMe3-n X n (n = 0−2; X = Cl, Br, OTf; Cn = 1,4,7-trimethyl-1,4,7-triazacyclon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 32 publications
(30 reference statements)
0
21
0
Order By: Relevance
“…4, the XPS spectra of the catalyst 3 gave a Rh 3d 5/2 binding energy of around 309.43 eV, indicating that the rhodium center was in the trivalent state. 19 More importantly, it was found that catalyst 3 had almost the same Rh 3d 5/2 electron binding energy as the parent Cp*RhTsDPEN (309.43 eV versus 309.38 eV), suggesting that the rhodium center within the FFMS silicate network retained its original chiral coordination microenvironment.…”
Section: Synthesis and Structural Characterization Of The Heterogeneo...mentioning
confidence: 96%
“…4, the XPS spectra of the catalyst 3 gave a Rh 3d 5/2 binding energy of around 309.43 eV, indicating that the rhodium center was in the trivalent state. 19 More importantly, it was found that catalyst 3 had almost the same Rh 3d 5/2 electron binding energy as the parent Cp*RhTsDPEN (309.43 eV versus 309.38 eV), suggesting that the rhodium center within the FFMS silicate network retained its original chiral coordination microenvironment.…”
Section: Synthesis and Structural Characterization Of The Heterogeneo...mentioning
confidence: 96%
“…A particularly clean method is the addition of triflic acid to a transition metal alkyl complex, with loss of alkane. For the platinum metals, this route has been used to prepare triflate complexes of Ru [2][3][4], Os [5,6], Rh [7], Ir [8], and Pt [9][10][11]. Formation of triflate complexes by addition of triflic acid to metal hydrides (with loss of H 2 ) is also possible; all the examples of this approach of which we are aware involve the element Ru [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Although intramolecular elimination is again the result, it will be seen that this system differs from Cp*Rh(PPh 3 )Me 2 in interesting ways. Recent publications by Flood and co-workers have focused on the organometallic chemistry of the CnRh moiety. The Cn ligand is bonded to the metal through three “hard”, poorly polarizable N atoms, devoid of π-backbonding capabilities.…”
Section: Introductionmentioning
confidence: 99%
“…This is in contrast with more conventional ligands like Cp, CO, PR 3 , etc., which are relatively “soft”, polarizable, and capable of accepting electron density from the metal by backbonding. It is hoped that the relatively hard Rh center that results from the coordination of the Cn ligand will significantly alter the chemistry of coordinated hydrocarbon ligands when compared to the behavior of related Rh complexes that are ligated by softer ligands 5a. Although it is not clear whether the effects arise from the altered hardness of the metal, several reports indicate important reactivity differences betweenCnRh and related CpRh and TpRh complexes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation